Accumulation and forage quality of wheatgrass species during the implantation stage under three seeding rate (Semiárida, 2019)
The objective of this work was to evaluate the accumulation and quality of the forage of tall wheatgrass, “criollo” wheatgrass and crested wheatgrass under seeding rate of 120, 250 and 400 viable seeds.m2. The experiment was carried out in INTA Anguil in a randomized block design. Four cuts were made in which dry weight was determined and in two of them the nutritional quality of the forage. The height of plants and the number of tillers were also determined. The means were compared by 5% DMS. In plant height only differences were recorded between species, while for the number of tillers there were no significant differences between species or densities. Considering the forage production, intermediate seeding rate would be the most suitable for tall wheatgrass and “criollo” wheatgrass, while the highest density would be for crested wheatgrass. Seeding rate did not affect the nutritional quality of the forage in any of the wheatgrass species. Regarding the species, tall wheatgrass was the most promising in forage production, but from the point of view of nutritional quality it was the lowest forage value.
Keywords: sowing; pasture; height; tillers; biomass; nutritive quality